2008
DOI: 10.1152/ajplung.00437.2007
|View full text |Cite
|
Sign up to set email alerts
|

Prostasin expression is regulated by airway surface liquid volume and is increased in cystic fibrosis

Abstract: Airway surface liquid (ASL) absorption is initiated by Na+ entry via epithelial Na+ channels (ENaC), which establishes an osmotic gradient that drives fluid from the luminal to serosal airway surface. We and others have recently reported that a protease/anti-protease balance regulates ENaC in human airway epithelial cells (HAEC) and provides a mechanism for autoregulation of ASL volume. In cystic fibrosis (CF), this balance is disturbed, leading to constitutive proteolytic activation of ENaC and the pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 50 publications
1
59
0
Order By: Relevance
“…2 A). However, the serine proteases that activate ENaC are up-regulated in CF airway epithelia (10,40) and neutrophil elastase, which also activates ENaC, is increased in CF airways (41)(42)(43). Thus, it is possible that the excessive protease up-regulation seen in CF airways (10,40) interferes with the normal regulation of ENaC by SPLUNC1 and other potential ENaC regulators, and thus, shifts the balance from anti-proteases and less ENaC activity to a protease-replete state with more ENaC activity, overwhelming the ability of SPLUNC1 to inactivate ENaC and contributing to CF airway surface liquid volume depletion.…”
Section: Resultsmentioning
confidence: 99%
“…2 A). However, the serine proteases that activate ENaC are up-regulated in CF airway epithelia (10,40) and neutrophil elastase, which also activates ENaC, is increased in CF airways (41)(42)(43). Thus, it is possible that the excessive protease up-regulation seen in CF airways (10,40) interferes with the normal regulation of ENaC by SPLUNC1 and other potential ENaC regulators, and thus, shifts the balance from anti-proteases and less ENaC activity to a protease-replete state with more ENaC activity, overwhelming the ability of SPLUNC1 to inactivate ENaC and contributing to CF airway surface liquid volume depletion.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, our data show that A1AT down-regulates both I amil values in vitro and Na 1 -dependent AFC across the distal lung epithelia of anesthetized mice in vivo. Recently, Myerburg and colleagues (45) reported that protease inhibitor, PN-1, another member of the SERPIN family, inhibited Na 1 currents across human airway epithelial cells isolated from CF lungs (45). Protease inhibitor PN-1, like A1AT, inhibits matriptase (45).…”
Section: Discussionmentioning
confidence: 99%
“…9 Prostasin, a trypsin-like serine protease, is a major channel-activating protease (CAP) of ENaC-mediated sodium currents in CF epithelia. [10][11][12][13][14] Attenuation of ENaC function by CAP inhibition is predicted to improve mucociliary clearance with potential downstream effects on pulmonary obstruction and clinical stability. Camostat is an inhibitor of prostasin that has been shown to inhibit ENaC function in vitro 15 and in vivo.…”
Section: Assessmentsmentioning
confidence: 99%